Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fpls.2016.01416
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of miRNAs and Their Target Transcripts between a Spontaneous Late-Ripening Sweet Orange Mutant and Its Wild-Type Using Small RNA and Degradome Sequencing

Abstract: Fruit ripening in citrus is not well-understood at the molecular level. Knowledge of the regulatory mechanism of citrus fruit ripening at the post-transcriptional level in particular is lacking. Here, we comparatively analyzed the miRNAs and their target genes in a spontaneous late-ripening mutant, “Fengwan” sweet orange (MT) (Citrus sinensis L. Osbeck), and its wild-type counterpart (“Fengjie 72-1,” WT). Using high-throughput sequencing of small RNAs and RNA degradome tags, we identified 107 known and 21 nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…For instance, miR396 controls leaf size by regulating expression of GROWTH REGULATING FACTORS (GRFs; Rodriguez et al, 2010); mutations in MIR319a lead to decreases in petal length and width (Nag et al, 2009). Omics-based studies have identified multiple fruit ripening-related miRNAs, including 28 miRNAs expressed during tomato fruit ripening (Zuo et al, 2012), 24 miRNAs differentially expressed in wildtype and late-ripening sweet orange (Wu et al, 2016), and 82 miRNAs closely associated with banana ripening (Bi et al, 2015). (Zhang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR396 controls leaf size by regulating expression of GROWTH REGULATING FACTORS (GRFs; Rodriguez et al, 2010); mutations in MIR319a lead to decreases in petal length and width (Nag et al, 2009). Omics-based studies have identified multiple fruit ripening-related miRNAs, including 28 miRNAs expressed during tomato fruit ripening (Zuo et al, 2012), 24 miRNAs differentially expressed in wildtype and late-ripening sweet orange (Wu et al, 2016), and 82 miRNAs closely associated with banana ripening (Bi et al, 2015). (Zhang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous fruit development-associated miRNAs have been identified in fruit-producing plants such as apple [ 19 ], grape [ 20 , 21 ], citrus [ 26 ], peach [ 23 ]. In this study, 84 known miRNAs belonging to 28 families and 16 novel miRNAs were identified in blueberry fruit.…”
Section: Discussionmentioning
confidence: 99%
“…41 miRNAs were differentially expressed between white fruit stage and blue fruit stage ( Table 2 ), suggesting that they might be involved in controlling the cellular and developmental processes during fruit maturation in blueberry. By comparing vco-miRNAs and the ones from other fruit-producing plants such as apple [ 19 ], grape [ 20 , 21 ], citrus [ 26 ], peach [ 23 ], tomato [ 31 ] and cucurbits [ 32 ], it was found that 21 miRNA families are more common across these fruit-producing plants, suggesting that they might play crucial and fundamental roles in fruit development and maturation in diverse plants. However, 7 miRNAs (such as miR2118, miR2603, miR6149, miR6478, miR7122, miR7693 and miR845) were found only in blueberry fruits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, because of its advantages in high throughput, high accuracy, and less sample, the deep sequencing has been widely used in many plants, such as Arabidopsis thaliana [ 23 , 24 ], Citrus sinensis [ 25 ], Cucumis sativus [ 26 ], Medicago truncatula [ 27 ], Oryza sativa [ 28 ], and Populus trichocarpa [ 29 ]. In citrus, deep sequencing studies has been reported in Citrus grandis [ 30 ], Citrus reticulata [ 31 , 32 ], Citrus sinensis [ 25 , 33 35 ], and Citrus trifoliate [ 36 ].…”
Section: Introductionmentioning
confidence: 99%